Impact of Social Support Ecosystem on Academic Performance of Children From Low-Income Families: A Moderated Mediation Model - Wen, Xiaoqiong; Li, Zhihua (Frontiers in Psychology, 2022)
This study conducted a questionnaire survey involving 513 children from low-income families (mean age = 13.25 ± 2.19 years) to explore the relationship between social support and academic performance as well as the mediating role of dispositional optimism and the moderating role of grit. A structural equation model analysis showed that: (1) social support has a significant positive predictive effect on academic performance and (2) dispositional optimism has a significant mediating effect on the relationship between social support and academic performance. Further, a moderated mediation effect test showed that grit moderates (3) the direct social support effect on academic performance as well as (4) the direct and indirect pathways among social support, dispositional optimism, and academic performance. The results indicate that social support is conducive to the development of dispositional optimism in children from low-income families, thereby improving their academic performance. At the same time, grit can enhance the positive impact of optimism on the academic performance of children from low-income families. This study has important theoretical and practical implications for effectively improving the academic performance of children from low-income families.